Prevalence and correlates of the supportive care needs of Italian early-stage melanoma patients in follow-up. Issue 6 (2nd November 2019) - Miniotti, Marco; Zeneli, Anita; Bassino, Stefania; Pavan, Sara; Ribero, Simone; Leombruni, Paolo
Abstract: Purpose: To describe the supportive care needs of early-stage Italian melanoma patients and identify the predictors of unmet needs. Design: Bicenter cross-sectional. Sample: Two hundred eight (TIS-T3) melanoma patients in follow-up. Methods: In person self-assessment procedures; the Supportive Care Needs Survey short-form 34, the Distress Thermometer and the Hospital Anxiety and Depression Scale were used. Results: Of the patients surveyed, 56% experienced at least one or more moderate-to-high unmet needs. Lack of melanoma-specific information and psychological support aids were the most intense sources of need. Being aged 60–69 years, retired and distressed predicted unmet needs. Conclusions: This study's results demonstrate the need to implement supportive care needs screening among Italian early-stage melanoma patients during follow-up and to improve patient information and psychological support. Implications for psychosocial providers or policy: Providing patients with a point person within the hospital staff who centralizes the demand and refers to appropriate interventions may help the management of unmet needs.